2021
DOI: 10.3389/fmicb.2021.763129
|View full text |Cite
|
Sign up to set email alerts
|

The Cytopathic Effect of Different Toxin Concentrations From Different Clostridioides difficile Sequence Types Strains in Vero Cells

Abstract: Clostridioides difficile is one of the leading causes of healthcare-associated diarrhea, with severity ranging from mild, self-limiting disease, to life-threatening toxic megacolon. C. difficile infection (CDI) pathogenesis is mediated by the TcdA and TcdB toxins. This work aimed to draw correlations between toxin levels, bacterial strains, and disease severity in 63 CDI patients. C. difficile typing was performed by multi-locus sequence types (MLST). Toxin concentrations were measured using the TOX A/B test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…We next assessed the impact of SCFAs on C. difficile toxin and spore production, which typically occur during stationary stage (60). We assessed toxin production in the presence of SCFAs using an in vitro cell rounding assay (61). After 24 hours of growth, we observed increased toxin by C. difficile strain 630 in the presence of all SCFAs, compared to BHI alone (Figure 3A, Dunnett's Test, p < 0.001).…”
Section: Butyrate Increases Toxin and Spore Production In C Difficilementioning
confidence: 96%
“…We next assessed the impact of SCFAs on C. difficile toxin and spore production, which typically occur during stationary stage (60). We assessed toxin production in the presence of SCFAs using an in vitro cell rounding assay (61). After 24 hours of growth, we observed increased toxin by C. difficile strain 630 in the presence of all SCFAs, compared to BHI alone (Figure 3A, Dunnett's Test, p < 0.001).…”
Section: Butyrate Increases Toxin and Spore Production In C Difficilementioning
confidence: 96%
“…We next assessed the impact of SCFAs on C. difficile toxin and spore production, which typically occur during the stationary growth phase ( 61 ). We assessed toxin production in the presence of SCFAs using an in vitro cell rounding assay ( 62 ). After 24 h of growth, we observed increased toxin by C. difficile strain 630 in the presence of all SCFAs, compared to BHI alone ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There has been previous research on the relationship between the levels of toxins produced by different strains of C. difficile and disease severity, but it has yielded contradictory results. However, a recent study that investigated the impact of different STs [ 142 ] found that, although there was no significant association between toxin levels and disease severity, ST 42 and ST 104, which produce high levels of toxins, had the most significant effects on cell proliferation, causing a reduction when compared to control cells. Additionally, ST 37 had a more severe impact on cell morphology.…”
Section: Virulence Factors and Toxin Productionmentioning
confidence: 99%